Pengaruh Corporate Social Responsibility Dan Mekanisme Corporate Governance Terhadap Nilai Perusahaan - Rika Astrinika; H. Sri Sulistyanto (JEMAP, 2018)
This study examines the influence of CSR and the mechanism of GCG on firm value. The main reasons are, first, disclosure of social responsibility is very important for the company's reputation. Second, CSR is no longer voluntary. Third, CSR disclosure can be linked to corporate governance. By using a sample of manufacturing companies listed on the Stock Exchange in 2011-2015, this study provides results that (1) disclosure has a positive and significant influence on firm value, (2) managerial ownership has a positive and insignificant influence on the value of the company, ( 3) institutional ownership has a negative and insignificant effect on the value of the company, (4) an independent board of directors has a positive and significant influence on the value of the company, and (5) the audit committee has a positive influence and significant influence on the value of the company